Mitigating undesirable impacts in the marine environment: a review of market-based management measures - Innes, James; Pascoe, Sean; Wilcox, Chris; Jennings, Sarah; Paredes, Samantha (Frontiers in Marine Science, 2015)
Internationally, marine biodiversity conservation objectives are having an increasing influence on the management of commercial fisheries. While this is largely being implemented through marine protected areas, the use of market based instruments (MBIs) has proved useful in other areas of fisheries and biodiversity conservation management. This paper explores the potential of MBIs as biodiversity conservation management tools for mitigating the undesirable impacts of fishing industries operating in the marine environment, examples of which are still relatively limited in the marine context. We assess the potential of several alternative measures by reviewing and considering the successes and limitations of previous applications and how these would translate in the case of commercial fishing. Several fishing methods and conservation values are considered and the circumstances in which MBIs may be most applicable are identified. Where appropriate, and by either replacing or (more likely) complementing existing management arrangements, MBIs have the potential to improve environmental performance. This has a number of implications. From the environmental perspective they should enable levels of undesirable impacts on conservation values such as sensitive habitat or protected species of turtles, marine mammals and seabirds to be reduced. MBIs can also increase management cost-effectiveness and reduce the costs imposed upon industry by allowing them greater flexibility when developing solutions. Further, in the increasingly relevant case of MPAs, the potential cost of structural adjustment packages to government may also be significantly reduced if improved environmental performance makes it possible for some industry members to continue operating.